2010
DOI: 10.1021/jp100960u
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Interfacial Binding between Single-Walled Carbon Nanotubes and Heterocyclic Conjugated Polymers

Abstract: Molecular dynamics (MD) simulations were performed to investigate the interfacial binding between the single-walled carbon nanotubes (SWCNTs) and conjugated polymers including polythiophene (PT), polypyrrole (PP), poly(2,6-pyridinylenevinylene-co-2,5-dioctyloxy-p-phenylenevinylene) (PPyPV), and poly(m-phenylenevinylene-co-2,5-dioctyloxy-p-phenylenevinylene) (PmPV). The intermolecular interaction energy between SWCNTs and polymer molecules was computed, and the morphology of polymers physisorbed to the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 53 publications
5
47
0
2
Order By: Relevance
“…In this regard, Foroutan el al. [50] have investigated the interfacial binding between the SWNTs and conjugated polymers including polythiophene (PT), polypyrrole (PP), poly (2,6-pyridinylenevinylene-co-2,5-dioctyloxy-p-phenylenevinylene) (PPyPV), and poly(m-phenylenevinyleneco-2,5-dioctyloxy-p-phenylenevinylene) (PmPV) and showed that the intermolecular interaction was strongly influenced by the specific monomer structure of conjugated polymer and nanotube radius.…”
Section: Dispersion Of Cnts By Polymermentioning
confidence: 99%
“…In this regard, Foroutan el al. [50] have investigated the interfacial binding between the SWNTs and conjugated polymers including polythiophene (PT), polypyrrole (PP), poly (2,6-pyridinylenevinylene-co-2,5-dioctyloxy-p-phenylenevinylene) (PPyPV), and poly(m-phenylenevinyleneco-2,5-dioctyloxy-p-phenylenevinylene) (PmPV) and showed that the intermolecular interaction was strongly influenced by the specific monomer structure of conjugated polymer and nanotube radius.…”
Section: Dispersion Of Cnts By Polymermentioning
confidence: 99%
“…Also, use of π-π interaction of aromatic rings in polymers is known to be effective for both binding carbon nanotubes (CNTs) and dispersing them without damaging the sp 2 structure and thereby interrupting CNT conjugation [23][24][25]. Therefore, aromatic rings on the polystyrene block should be effective for stacking the SIS molecules onto the CNT surface via π-π interaction; dispersing the CNTs; MWNTs were mixed and ground with ionic liquid (2.5 times vs. MWNTs) using a pestle and mortar for 30 min.…”
Section: Complete Gelation Of Mwnts and Ionic Liquid Occurred When A mentioning
confidence: 99%
“…A low density CNTs forms small CNT/OSC interfacial area while high density CNTs creates large interfacial area with OSC. It has been suggested from the molecular dynamics simulation and NMR spectroscopy that2 a π-π interaction exists between CNT/OSC [19][20][21]. In addition, CNT has a field emission property due their one-dimensional structure [22].…”
Section: Introductionmentioning
confidence: 99%